Studi Literatur : Kepemimpinan Tim Dalam Pengembangan Organisasi - Nuril Shofiyah; Aef Fikrial Barlean; Mochammad Isa Anshori (Jurnal Riset dan Inovasi Manajemen, 2023)
This research is motivated by several crucial roles in achieving effective team performance. In understanding team leadership, a strong theoretical and conceptual framework is needed. Team leadership also influences team performance motivation. Effective leaders can influence team motivation through effective communication, providing positive feedback, providing rewards and recognition, and creating a supportive work environment. The key factors that influence great team performance also need attention. factors such as team trust, collaboration, effective communication and leader support are major factors that contribute to great team performance. This study uses the literature study method and aims to determine the role of leadership in organizations. In conclusion, team leadership plays an important role in achieving effective team performance in organizations. By understanding a strong theoretical and conceptual framework, leaders can develop the practical and strategic insights needed to lead teams effectively. Effective leaders influence team performance motivation, manage conflict, build teamwork, and create a supportive work environment. The importance of effective team performance is also underpinned by the key factors that influence great team performance. In practice, leaders must be able to apply these insights practically to achieve the desired results.